Detection of human papillomavirus DNA in peri-tumor tissues and pelvic lymph nodes as potential molecular marker of micrometastasis in cervical cancer - Tortora, Marianna (Infect Agent Cancer, 2016)
BACKGROUND: The association between high risk human papillomaviruses (HPV) and cervical cancer has been firmly established. HPV genome is present in nearly all cases of cervical cancer and detection of viral DNA could therefore be used as a surrogate marker of micrometastasis in peri-tumor tissues and lymph nodes. METHODS: We analyzed primary cervical carcinomas, peri-tumor biopsies and pelvic lymph nodes in 20 women with invasive cancer (FIGO stage I-II) who underwent radical pelvic surgery and lymphadenectomy. HPV DNA was searched by broad spectrum PCR in 142 DNA samples extracted from paraffin embedded tissues. Viral genotypes were identified by direct sequencing analysis. RESULTS: HPV DNA sequences were identified in all available primary cervical tumors (n = 15). The most common genotype was HPV16 (60 %), followed by HPV18 (20 %), HPV35 (7 %), HPV45 (7 %) and HPV66 (7 %). Seven out of 20 (35 %) women had metastatic spread in peri-tumor tissues and/or lymph nodes, as determined by histology. HPV DNA was detected in all histological positive samples as well as in 16 and 25 % of histological negative peri-tumor tissues and lymph nodes, respectively. Three out of 20 (15 %) women without histological evidence of metastatic spread had HPV-positive lymph nodes. HPV genotype was found always concordant between primary tumor and metastatic lesions. The remaining 10 women (50 %) were histology and HPV-negative in all peri-tumor biopsies and lymph nodes analyzed. CONCLUSIONS: Evaluation of HPV DNA in peri-tumor tissues as well as pelvic lymph nodes could be a sensitive marker to identify micrometastasis or isolated tumor cells and to monitor the risk of disease recurrence in women with cervical cancer.